Caspase-11 Mediated Cell Death Contributes to the Pathogenesis of Imiquimod-Induced Psoriasis - Lavelle, Edward; Creagh, Emma; Munoz-Wolf, Natalia (My University, 2019)
Inflammasomes are multiprotein complexes that respond to infection or injury to activate inflammation. Inflammatory caspases, caspase-1, 4 and 5 in humans, and their murine orthologues caspase-1 and 11 are crucial components of inflammasomes, responsible for the maturation and secretion of IL-1β and IL-18, and for pyroptosis (inflammatory cell death) (Creagh, 2014). Psoriasis is a chronic inflammatory skin condition with a range of clinical manifestations. The most common manifestation is chronic plaque psoriasis, where the adaptive immune response predominates. However innate and autoinflammatory events, governed by IL-1β (Martinez-Quiles and Goldbach-Mansky, 2018), prevail in pustular forms of psoriasis (Liang et al., 2017).
PUBLISHED
DOI: 10.1016/j.jid.2019.05.010
Keywords: Caspase-1 and -11 (casp1/11); Imiquimod (IMQ); Double knockout (DKO); Terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL); Lipopolysaccharide (LPS); Lactate dehydrogenase (LDH); Bone marrow derived macrophage (BMDM)